The SENAM ERGONOMIK TERHADAP KUALITAS TIDUR PADA LANSIA: THE EFFECT OF ERGONOMIC EXERCISES ON SLEEP QUALITY IN THE ELDERLY - Desi Br Sembiring (LPPM STIKes Buleleng, 2026)
Introduction: Poor sleep quality—characterized by frequent awakenings and difficulty falling asleep—impacts the body's balance. It entails physiological and psychological consequences such as fatigue, elevated blood pressure, anxiety, and reduced physical and emotional activity. Methods: This study employed a quasi-experimental design with a pretest-posttest approach. The study population consisted of elderly individuals within the working area of ​​the Medan Tuntungan Community Health Center. A sample of 34 elderly participants was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data analysis was conducted using the paired t-test to examine differences before and after the intervention. Results: The findings indicate that the elderly participants' sleep quality was poor prior to the ergonomic exercise intervention (mean score: 13.21) and improved to a good level following the intervention (mean score: 5.35). Conclusion: Statistical analysis yielded a p-value of 0.000 (<0.05), indicating that ergonomic exercise has a significant effect on sleep quality among the elderly.